The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1111/j.1365-2672.2004.02485.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bacteriophage and enteric virus removal in pilot scale activated sludge plants

Abstract: Aims:The aim of this experimental study was to determine comparatively the removal of two types of bacteriophages, a somatic coliphage and an F-specific RNA phage and of three types of enteric viruses, hepatitis A virus (HAV), poliovirus and rotavirus during sewage treatment by activated sludge using laboratory pilot plants. Methods and Results:The cultivable simian rotavirus SA11, the HAV HM 175/18f cytopathic strain and poliovirus were quantified by cell culture. The bacteriophages were quantified by plaque … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 37 publications
2
32
0
2
Order By: Relevance
“…Coliphage was suggested as a better indicator for human virus because it shares decay characteristics that are similar to those of human viruses (1,2,11,22). Several studies, including our own study of the southern California coast, showed a correlation between coliphage and PCR-detectable human viral genome (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coliphage was suggested as a better indicator for human virus because it shares decay characteristics that are similar to those of human viruses (1,2,11,22). Several studies, including our own study of the southern California coast, showed a correlation between coliphage and PCR-detectable human viral genome (16).…”
Section: Discussionmentioning
confidence: 99%
“…1). The principle tributary of Newport Bay is San Diego Creek, which accounts for 122 square miles (316 km 2 ), or about 80%, of the Newport Bay watershed. Other drainage areas include the Santa Ana-Delhi Channel, the Big Canyon Wash, and some additional small tributaries.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The titre of poliovirus was determined by plaque assay in BGM cells as previously described (Arraj et al 2005).…”
Section: Cell Culture Infectionmentioning
confidence: 99%
“…A range of studies, performed at both pilot-scale and within full-scale municipal wastewater plants, have demonstrated that microbial removal in MBR systems is more effective than in conventional activated sludge treatment systems (Arraj et al, 2005;Ottoson et al, 2006;Francy et al, 2012;Marti et al, 2011). Further, MBR systems have been shown to remove microorganisms that are greater in size than the membrane filter pores.…”
Section: Introductionmentioning
confidence: 99%